Smart Card Implementation Model - Lee, Chin Huat (2000)

(untitled)
Smart card (intelligent card) systems evolved in the 1970s and progressed through the 2000s, however, their globalization and potential has not yet been achieved. In some countries, France for example, they have been accepted and implemented to a very high degree, while in others the technology is just emerging. The present research analyses these underlying principles from a business perspective and proposes a set of procedures (a implementation plan) for the design of smart card applications. These procedures are based on the market overview and market prospective from the previous cases as a guideline to implement a smart card. I describe a generic, scalable plan that may be applied to future smart card operating systems, interfaces, and implementation schemes.